DENTAL HEALTH SERVICE DURING PANDEMIC COVID-19 : A LITERATURE REVIEW - Nabila Rizkika; Matheus Sakundarno Adi (ODONTO : Dental Journal, 2021)
ABSTRACTBackground: COVID-19 pandemic is a new challenge for dentist. Doctor-patients contact, aerosol formed during treatment, and contact with contaminated instruments are the transmission route for COVID-19 infection. Several guidelines and suggestion regarding infection control measures have been released, but the standard protective measures in daily clinical work are not effective enough to prevent the spread of COVID-19. Aim To provide an overview of the measures that can be made in order to prevent the spread of COVID-19 in dental health services Method: Systematic literature review used literature search methods in electronic databases: Google Scholar, Science Direct, and PubMed. The keywords were “COVID-19 and dental practice” and “dental practice during COVID-19”. The inclusion criteria for selection of scientific articles were years of publication from January 2020 to October 2020, published in English and full paper available. Out of 44 articles that have been screened, nine articles have been included in this reviewResult: The nine articles that were collected have already pointed out some necessary measures. Patients screening and triage are the first steps in selecting emergency cases, minimal invasive procedure are the principle in every dental treatment, and the use or personal protective equipment for dentist and team is an absolute requirement before performing any dental treatment.Conclusion: Protecting the oral environment through dental checks-up with preventive measure is important during the pandemic.